توہین انبیاء کی عالمی مہم محرکات،اسباب،اور سدِ باب:ایک تحقیقی جائزہ: Global Campaign about Prophetic Blasphemy: Motivations, Causes, and Solutions - A Research Overview - Faran Anwar,; Dr. Hafiz Faiz Rasool,; Muhammad Affan Ul Haq, (International Research Journal of Arabic and Islamic Studies, 2024)
With the creation of the universe, Allah Almighty started a blessed series of Prophets for the spiritual training of people in it, and in different periods The Prophets and The Russell’s were engaged in the work of the people who paid special attention to the moral training of the people. Some people responded to their invitation and continued to achieve success in their lives, while others refused and put the shackles of failure around their necks. In the same way, there has been a section of people who have always tried to extinguish the light of God and have devoted all their efforts to prevent the message of God from reaching the people. In order to achieve this goal, they used various tactics and even started libeling The Prophets and The Russell’s in different ways. This article discusses the background of the whole scenario, when it started and when it accelerated and the underlying motives have also been clarified It also explains the causes of the blasphemy of The Prophets, the motives behind which these Holy Beings are being targeted and insults are being inflicted on them day after day. Finally, in order to prevent this, the sensitivity of the issue has been examined first and it has been clarified that such measures pose a serious threat to world peace and practical recommendations have been made to address them.